CORRUPTION IN THE QUR`AN: CAUSES, SANCTIONS, AND ALTERNATIVE SOLUTIONS BASED ON THE QUR`AN - Wendi; Riyani (Darul Hikmah: Jurnal Penelitian Tafsir dan Hadits, 2023)
Corruption is an act that has existed since the time of the Prophet Muhammad Saw and even today corruption still occurs. The perpetrators can be anyone from various divisions and hierarchies of humanity, from ordinary people, officials, and even conglomerates. Based on these reasons, it is important to conduct this study. This research is a library research – using a thematic interpretation approach. The conclusion of this article is that the cause of corruption is influenced by two factors, namely greed and the lack of supervisory mechanisms. The sanction offered by the Qur'an is literally cutting off the hand, but it can also be understood with the meaning of ta'zir, according to the crime committed. Then the alternative solution offered by the Qur'an in minimizing corruption is to instill awareness of every individual about human nature on earth and to raise government awareness of the importance of their authority in eradicating corruption.